Grey economy, crisis and transition in Serbia - Novaković, Nada G. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
In this article the author uses a sociological approach to the study of the gray economy in a society in transition, ie in Serbia. It was after 1990 created the society of the capitalist periphery. Special emphasis is placed on socio-economic development from 2007 to 2012. This is the time just before the onset of the global economic crisis, and its deepening and expansion. In Serbia, then terminated the privatization and transition of society. The main thesis is: the main factors of the emergence and spread of the shadow economy are primarily domestic origin. The world crisis gives them just a special stamp. The most important factors of gray economy are systemic in nature. These are the following: nature of the transition, selected and implemented the concept of privatization and the character of political and economic elites. They form the core of the new capitalist class in Serbia, which is dependent on the international centers of financial, political and military power. The concept of the underground economy refers to the following: unauthorized activities outside the law and norms of business ethics, of fine work, avoidance of tax and other obligations, to those who are committed to the area of ​​bribery and corruption, small, large and systemically organized kkriminala. This applies to business and employment outside the law and illegal financial transactions, on the one hand, and the crime of various kinds, on the other hand. The most widespread are two forms of the gray economy are the production and sales of products and services and has moonlighting. The author emphasizes the multidimensionality of the gray economy and is committed to an interdisciplinary approach to its study. Therefore, the data sources used by a variety of rzultata official statistics on economic, demographic, historical, politicology and related research on the informal economy and its development. Special attention is paid to the results of sociological research on the structure of society, inequality, unemployment and poverty of citizens. Comparison of these phenomena, primarily volume, dynamics and growth resulting from the informal economy, with countries in the region and the world are not only necessary but also fruitful. The first part lists the most important systemic factors origin and growth of the gray economy in Serbia. They are numerous, but the article states the following: 1. the neo-liberal model of social transition; 2. the privatization of social capital based on the "shock privatization"; 3. the collapse of the welfare state and dwindling acquired economic and social rights of citizens; 4.uticaj "international community"; 5.the low activity rate and employment rate of working age; 6. high and mass unemployment; 7. the low rate of labor productivity; 8. the absence of the rule of law and institutions for efficient functioning of the market economy; 9. restrictive labor and social legislation; 10. the tax system; 11. poverty (un) employed population and 12. violated the civil and business ethics (bribery and corruption). Each of these phenomena are explained, describes and compares the regional and wider levels. The second part relates to the most important winners and losers of the gray economy in a society in transition. It lists the most important positive and negative consequences of participation in the informal economy zapojedince, social groups and society as a whole. It describes the scope and types of activities of the gray economy in total employment, GDP growth, the impact on inflation, inequality, the country's debt and others. Points out the advantages and disadvantages of illegal activities for entrepreneurs, employees, the state and society as a whole. Finally, he concludes his investigation statement that prevailing negative over the positive effects of the gray economy. Along the way, it is emphasized that the political will of the ruling class and international pushes down on it, to the fullest extent, depends on the start ozbiljnh efforts to reduce gray economy in a socially tolerable measure.
Keywords: transition; poverty; unemployment; crisis; shadow economy